(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the requirements for the personality of today’s teachers, their level of knowledge, the need to constantly work on themselves, and the fact that this aspiration serves as the basis for a bright future of our people, our nation, the socio-pedagogical views of our great scholars. This article also explains the classification of pedagogical methods.